Economic Analysis, Innovative Educational Models and Pragmatic Sustainability: The Case Study of a Photovoltaic System on a Public Building - D’Adamo, Idiano; Ozturk, Ilhan; Passarelli, Federico; Salvati, Christian (International Journal of Energy Economics and Policy, 2025)
The development of renewable energy has changed the utility sector, leading to a change in the interests of companies operating in the sector. The prosumer is a new emerging figure that can enable citizens and businesses to be an integral part of this change. In this context public administrations can play a key role and this study aims to assess the profitability of a photovoltaic (PV) system located in a public building (secondary school) in Italy. This analysis is integrated within an innovative teaching model that aims to stimulate the problem-solving competence of university students. The results show that the implementation of the PV system is characterised by important economic results with profits ranging from 2866 to 5670 €/kW in a 97 kW plant and from 2065 to 4012 €/kW in a 168 kW plant with a fundamental role played by the percentage of self-consumption and the avoided cost in the bill. The emission reduction in the 1st-year ranges from 56.6 to 98 tCO2eq. Pragmatic sustainability can support the decarbonisation of our energy system by involving young people in the choices and favouring social models that reward their skills.